2021
DOI: 10.3390/app11052370
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Instance Weighting-Based Deep Transfer Learning Network for Intelligent Fault Diagnosis

Abstract: Fault diagnosis is a top-priority task for the health management of manufacturing processes. Deep learning-based methods are widely used to secure high fault diagnosis accuracy. Actually, it is difficult and expensive to collect large-scale data in industrial fields. Several prerequisite problems can be solved using transfer learning for fault diagnosis. Data from the source domain that are different but related to the target domain are used to increase the diagnosis performance of the target domain. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…After adjusting the sample weight, the sampling training process using the improved LM algorithm is shown in Figure 3. From Figure 4, when the unimproved neural network is trained 100 times, there is still a big gap from the error of 10 -2 , and the neural network combined by the SOM method and the LM method, convergence is reached after 20 trainings [52][53][54][55][56][57][58] . Using the above combination of SOM method and LM method, the training process is shown in Figures…”
Section: Resultsmentioning
confidence: 99%
“…After adjusting the sample weight, the sampling training process using the improved LM algorithm is shown in Figure 3. From Figure 4, when the unimproved neural network is trained 100 times, there is still a big gap from the error of 10 -2 , and the neural network combined by the SOM method and the LM method, convergence is reached after 20 trainings [52][53][54][55][56][57][58] . Using the above combination of SOM method and LM method, the training process is shown in Figures…”
Section: Resultsmentioning
confidence: 99%
“…However, negative transfer may occur if source and target domains have significant differences; i.e., if domain-specific samples have large discrepancies in their probability distributions [18]. In other words, bringing source domain knowledge into the target task does not help, but rather hinders performance.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, bringing source domain knowledge into the target task does not help, but rather hinders performance. The effect of negative transfer has been noted in several transfer-learning-enabled fault diagnosis applications [15,18,19], inspiring researchers to examine the causes of negative transfer. A review can be found in [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhou et al [21,22] proved that it may be better to ensemble many instead of all of the neural networks and decision trees from the point of view of regression and classification, and proposed an algorithm called GASEN and GASEN-b, which uses a genetic algorithm to improve weights. Lee et al [23] proposed a multi-objective instance weight transfer learning network to solve the problem of fault diagnosis. The effectiveness of the proposed algorithm was verified by industrial robot and spot-welding experiments.…”
Section: Introductionmentioning
confidence: 99%